Meta-Analysis the Effect of Combination Oral Contraceptive on the Risk of Venous Thromboembolism and Stroke in Family Planning Acceptors - Sari, Putri Yunita; Pamungkasari, Eti Poncorini; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: The global percentage of con